Batalha dominação: ritmo, poesia e gêneros dissidentes no Largo da São Bento - SP - Borges, Lais Gomes [UNIFESP] (2021)
This work focuses on “Domination Battle” performances, a freestyle rhyme battle starring women, people non-binary and gender dissidents, held at Largo São Bento, in the central region of the city of São Paulo. Derived from the hip-hop movement, freestyle battles consist of challenges between MCs responsible for creating freestyle versus provoking their opponents or developing a theme suggested by the public. Since the 1980s, these performances have been produced by the hip-hop scene almost entirely by heterosexual cisgender men. In recent years, however, the participation of women and LGBTQIA+ people has been growing, as in the case of “Domination”, affecting both the occupation of public spaces in the city and the conventional way of doing rhyme battles. As a result, networks of sociability and solidarity alternative to the traditional segments of the Hip-hop movement are becoming denser, as well as their aesthetic and political inflections. Approaching this scene, this dissertation privileges dialogues with black intellectuals, transfeminists and lesbians authors about racial, gender and social inequality issues.